The gut-microbiome as a target for the treatment of schizophrenia: A systematic review and meta-analysis of randomised controlled trials of add-on strategies - Minichino, A; Brondino, N; Solmi, M; Del Giovane, C; Fusar-Poli, P; Burnet, P; Cipriani, A; Lennox, B (Elsevier, 2020)
The gut-microbiome has been hypothesised as a novel potential target for intervention for schizophrenia.